Tinjauan Kesenjangan Implementasi MARPOL Annex I terhadap Kasus Tumpahan Minyak di Kabupaten Bintan - Widia Novia Putri; Tipa Sapitri (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
Bintan Regency, as a coastal area with a strategic geographical location as an international shipping route, is vulnerable to marine pollution caused by oil spills. Repeated incidents throughout 2023-2025 show that this problem has not been resolved. The purpose of this study is to evaluate the effectiveness of the implementation of MARPOL Annex I as a regulation that prevents pollution caused by oil spills at sea, particularly in Bintan Regency. This study identifies gaps in the implementation of regulations at the national level and formulates a more integrated form of prevention through strengthened supervision and the application of technology. The method used is a qualitative descriptive method through a literature review approach, with secondary data from scientific journals, articles, media reports, YouTube, and other supporting documents related to the incident. The results of the study show that: first, mitigation efforts are still focused on post-spill responses, such as manual cleanup involving institutions and the community. Second, weak border patrols make it difficult to find the perpetrators. Third, Bintan Regency has not utilized technology such as blockchain as a potential tool that can help prove ship compliance with MARPOL Annex I. Although MARPOL Annex I has been implemented in accordance with national regulations, its implementation has proven ineffective as spills continue to recur to this day. Therefore, changes are needed in terms of prevention through integrated maritime surveillance and the introduction of digital technology for reporting ship compliance with MARPOL Annex I in the Bintan Regency area.